Occurance, pathogenicity, characterization of Fusarium fujikuroi causing rice bakanae disease from Odisha and in vitro management - S, Raghu; Yadav, Manoj K; SR, Prabhukarthikeyan; Baite, Mathew S; Lenka, Srikanta; Jena, Mayabini (ORYZA-An International Journal of Rice, 2018)
The present investigation was carried out to asses the incidence of bakanae disease in Odisha, characterization of the isolates and its management with fungicides. The disease incidence ranging from 1-25.50 percent on different rice varieties was recorded in five districts mainly, Cuttack, Sambalpur, Bargarh, Ganjam and Jajpur. These regions were identified as new hot spots for the disease. The disease was observed to a significant extent in most of the commercially growing varieties with maximum disease incidence on Pooja (19.0 % and 24.5% respectively for two seasons). A significant variation was observed among the isolates with respect to cultural, morphological characters and degree of pathogenicity. All the ten isolates were grouped into highly virulent group. The amplification of tef-1alpha gene generated approx 700 bp bands. In phylogenetic analysis, based on tef-1alpha gene region, overall two major groups were formed. The F.fujikuroi isolates FJ1 (Kisannagar), FJ2 (Khurda), FJ3 (Tangi-Chodwar) and FJ9 ( Chandikole) belonged to same group whereas FJ4 ( Cuttack), FJ5 ( Jajpur), FJ6 ( Kisannagar-2), FJ7 ( Sambalpur), FJ8 ( Bargarh) and FJ10 (Ganjam) are in a separate group with other world isolates. Among the ten systemic fungicides tested, all found effective with 100 percent reduction in mycelial growth. All the three tested Trichoderma spp. were found effective under in vitro with complete inhibition and lyses of the pathogen mycelium. Seed treatment with Carbendazim 50 % WP @1 g/kg of seeds found effective with maximum germination, vigor index and disease reduction.